PENGARUH KINERJA PELAYANAN (SERVICE PERFORMANCE) TERHADAP LOYALITAS DENGAN VARIABLE ANTARA KEPUASAN KONSUMEN NASABAH BANK JATIM - Bambang Setiyo Pambudi (Neo-Bis, 2008)
One of the service quality measurement was Servqual ( Service Quality), which was developed by Parasuraman, Zeithaml, and Berry., they had an apinion that in evaluating service quality, consumer compared between expected service quality and perceived service quality. Based on that theory, this research aimed to test the influence of service performance  to the customer loyalty, tested the influence of service performance to the consumer satisfaction, tested the influence of satisfaction to the bank customer loyalty and described the comparison of the direct and indirect influences of service performance to the bank customer  of Bank Jatim in Bangkalan. This research used path analysis. Conducted in three branches of Bank Jatim in Bangkalan. Result of research indicated that the interaction between service performance and customer satisfaction as moderator variable could explain the customer loyalty varians more than each variable.